Non-polar and polar chemical profiling of six Casearia species (Salicaceae). (December 2019) - Anhesine, Naira Buzzo; Bueno, Paula Carolina Pires; Torres, Roseli Buzanelli; Lopes, Norberto Peporine; Cavalheiro, Alberto José
Abstract: Six species of Casearia ( C. decandra, C. grandiflora, C. javitensis, C. arborea, C. lasiophylla and C. ulmifolia ) were chemically investigated in their non-polar and polar constituents. To this purpose, leaf extracts were analyzed by Gas- (GC) and Liquid-Chromatography (LC) coupled with Mass Spectrometry (MS). Twenty compounds, mainly identified as terpenes, fatty acids and hydrocarbons, and differentially expressed in the six species, were detected in the non-polar extracts. Fourteen compounds, among which glycosylated flavonoids and clerodane-type diterpenes, were tentatively identified by LC-MS/MS analysis in the leaf ethanol extracts. Highlights: Six species from the Casearia genus were chemically investigated. The chemical profile of C. javitensis and C. ulmifolia is reported for the first time. Glycosylated flavonoids and clerodane-type diterpenes were identified in polar leaf extracts.